GURU PROFESIONAL : MENGGALI KOMPETENSI DAN MENGASAH KARAKTERISTIK - Ta’ti Mamlakah; Suklani Suklani (CV. ADIBA AISHA AMIRA, 2024)
Quality education requires the central role of professional teachers who have strong competence and inherent characteristics. Exploring professional teacher competencies involves efforts to increase relevant pedagogical knowledge and skills. Competent teachers have a deep understanding of the subjects they teach as well as effective teaching methods. They can implement innovative teaching strategies, manage classes well, and facilitate student-centered learning. In addition, professional teachers also have the ability to integrate technology in the learning process to increase student engagement and achievement. Apart from competence, honing characteristics is also important in forming quality professional teachers. Characteristics such as integrity, empathy, effective communication, and leadership and collaboration skills are determining factors in forming positive relationships with students, parents, and colleagues. Professional teachers who have these characteristics can create an inclusive learning environment, support the holistic development of students, and build strong partnerships with education stakeholders.